KEGIATAN USAHA PENGGILINGAN DAGING PT. SOLO INDAH DI KELURAHAN LOLU SELATAN KOTA PALU - Moh Akbar Lagina; Ahmad Fahrozi; Gresya Yulian Masa; Riska Amelia; Nuraisyah Nuraisyah; Syarif Permana Salingkat; Gita Farista (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Entrepreneurship is a creative and innovative ability that is used as a basis, tips, and resources to find opportunities for success. When compared to developed countries in the world, the number of entrepreneurs in Indonesia is still very low, the entrepreneurial intention model has been proposed as a better alternative to predict entrepreneurial activity.This study aims to determine how new entrepreneurs identify business opportunities based on creativity and entrepreneurial innovation.The purpose of this study is to analyze the factors that influence the success of meat grinding entrepreneurs in the city of Palu, by conducting direct observation methods to meat grinding business owners through questionnaires covering managerial, marketing, and operational aspects. In addition, the SWOT analysis identifies untapped market opportunities, such as the development of processed meat products and partnerships with local restaurants. This study recommends innovation to increase competitiveness in the market. These findings are expected to be a reference for new entrepreneurs in building a meat grinding business.This study cannot be said to be a complete picture of how the opportunity identification process is carried out by entrepreneurs, because each field has different conditions and problems so that further research is still needed.